2007
DOI: 10.1097/01.rhu.0000255688.83037.42
|View full text |Cite
|
Sign up to set email alerts
|

Is Osteoporosis Generalized or Localized to Central Skeleton in Ankylosing Spondylitis?

Abstract: Sparing of distal regions such as the as radius suggests that osteoporosis might be due to localized effects of inflammatory activity or immobility rather than a systemic effect. Both increased resorption and decreased formation might be involved in the pathogenesis of osteoporosis. Radius BMD may not be appropriate to evaluate bone loss in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
2
12
1
3
Order By: Relevance
“…Apart from a cross-sectional design the limitation of this study is the lack of data for bone turnover markers, parathyroide hormone or vitamin D3, which could have revealed a better insight of association between activity parameters of both osteoporosis and AS [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a cross-sectional design the limitation of this study is the lack of data for bone turnover markers, parathyroide hormone or vitamin D3, which could have revealed a better insight of association between activity parameters of both osteoporosis and AS [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although it could appear paradoxical, excessive bony proliferation and osteoporosis occur simultaneously in patients with AS, suggesting uncoupling of bone formation and bone resorption processes [1,6,18]. In contrast to some clinical studies [31,32] stating that osteoporosis in AS is mainly located in the axial skeleton, other authors [28,33] have observed that bone loss also occurs in the appendicular skeleton. Several studies [10,23,[34][35][36][37] have shown a significant correlation between the markers of bone turnover, levels of pro-inflammatory cytokines [i.e., IL-6 and tumor necrosis factor (TNF)-α], and acute-phase reactants such as erythrocyte sedimentation rate and C-reactive protein, suggesting that the systemic inflammatory mediators may be involved in the pathogenesis of osteoporosis in patients with AS.…”
Section: Spinal Remodeling In Asmentioning
confidence: 98%
“…As well known bone turnover markers, OC [26][27][28][29][30][31][32][33][34][35][36][37][38] (supplemental data 2) and ALP 29,32,36,[39][40][41] (supplemental data 3) have been frequently assessed in AS in former studies; however, to our knowledge, they have not yet been evaluated in parallel with other markers in the Wnt signaling pathway. OC expression was similar between AS patients and controls.…”
Section: Discussionmentioning
confidence: 99%